GIANT PITUITARY MACROADENOMA MASKED BY BILATERAL RETINAL DETACHMENT - Lee, Joel Xiang Loong; Oon, Jen Hoong; Tob, Noor Hafis Md; Tong, Chin Voon; Verghis, Melissa; Lee, Siow Ping (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Pituitary adenomas are benign tumours that encompass 10-20% of intracranial neoplasms. About 25-35% are clinically non-functioning pituitary adenomas (NFPA). Giant pituitary adenomas (diameter ≥4 cm) comprise approximately 5% of all pituitary tumours and usually present with mass effects on the neighbouring structures causing visual impairments, headaches and cranial nerve dysfunction. We present a case of giant pituitary macroadenoma with late presentation, being masked by bilateral retinal detachment. CASE A 39-year-old male with past history of bilateral retinal detachment following motor vehicle accident presented with progressive deteriorating vision for the past 3 years. This was initially attributed to retinal detachment/retinal scar. He then had frequent falls and headaches for the past 2 months. Cranial MRI showed a large pituitary adenoma measuring 6.3 x 5.7 x 5.9 cm with compression to the frontal and parietal lobes, optic chiasm and lateral ventricles bilaterally. He underwent two debulking surgeries. Post-surgery imaging showed minimal changes in tumour size. Histopathology examination showed pituitary adenoma with low ki67. Clinically and biochemically, he had panhypopituitarism with thyroid stimulating hormone (TSH), adrenocorticotropic hormone (ACTH) and gonadotrophins insufficiency. He is now on thyroxine, hydrocortisone and testosterone replacement. A multidisciplinary team meeting discussion concluded that a third debulking surgery by a high-volume surgeon followed by radiotherapy is the best option for the patient. CONCLUSION This is a case of NFPA complicated by progressive visual impairment which was masked by bilateral retinal detachment. We highlight the difficulty of detecting NFPA early in this patient in view of his visual history.